Zinc Oxide Nanoparticles as The Anti-Bacterial Tool: In Vitro Study: Life Sciences-Nanotechnology - Satpathy, Gargibala; Rebecca, Jayanti; Sahu, Umabati; Das, Ipsita; Manikandan, E. (International Journal of Life Science and Pharma Research, 2023)
A new class of metal oxide nanoparticles has recently been found to be widely used in various health-related research. In particular, Zinc Oxide (ZnO) nanoparticles have occupied a prominent status due to their unique chemical and electrical properties. In our study, we aim to reveal the anti-bacterial effect of these nanoparticles. The antibacterial activity of zinc oxide (ZnO) nanoparticles against isolated pathogenic Escherichia coli (strain MTCC 723) was determined from our study. The antimicrobial properties of ZnO were also determined by adjusting the concentration of ZnO nanoparticles. By sonicating ZnO nanoparticles in water, a homogenized suspension was created, and the infusion was made at 50 – 150g/ml concentrations. Anaerobic conditions were used to culture the pathogenic strain of microbial species, and DNA was extracted using an extraction kit. For testing, equalized standard dilutions of cultivated bacteria were utilized. The anti-bacterial capabilities of zinc oxide (ZnO) nanoparticles against bacteria were measured using spectroscopic and diffusion experiments. ZnO nanoparticles with a diameter of 50 nm and a concentration of 150 g/ml lysed Escherichia coli DNA and cells. According to the findings, ZnO nanoparticles with a concentration of 150 g/ml had significantly more vigorous activity against Escherichia coli. The agar diffusion method was used to quantify the anti-bacterial activity of zinc oxide (ZnO) and the quality and amount of DNA extraction in the presence of ZnO nanoparticles (ZnO). The pathogenic Escherichia coli cells and the gene DNA are killed at the optimal dose. This study aims to know the anti-bacterial properties of ZnO nanoparticles against pathogenic Escherichia coli cells. The optimization of ZnO nanoparticles concentration against its effect on Escherichia coli cells is the next aim of this study.